How does childhood bilingualism and bi-dialectalism affect the interpretation and processing of pragmatic meanings? - Antoniou, Kyriakos; Veenstra, Alma; Kissine, Mikhail; Katsos, Napoleon (My University, 2020)
Recent research has reported superior socio-communicative skills in bilingual children. We examined the hypothesis of a bilingual pragmatic advantage by testing bilingual, bi-dialectal and monolingual children on the comprehension and processing of various pragmatic meanings: relevance, scalar, contrastive, manner implicatures, novel metaphors and irony. Pragmatic responses were slower than literal responses to control items. Furthermore, children were least accurate with metaphors and irony. Metaphors and irony were also the most difficult to process; for these meanings, pragmatic responses were slower than literal responses to the same critical items. Finally, pragmatic performance positively correlated with working memory. Despite this variation, we found no bilingual or bi-dialectal advantage over monolinguals in pragmatic responses or speed of pragmatic processing. This was also true despite bilinguals' and bi-dialectals' lower vocabularies as measured by formal tests. We conclude that bilingual children exhibit monolingual-like pragmatic interpretation, despite their often-reported weaker language knowledge in the target language.
Keywords: pragmatic processing; pragmatic interpretation; implicature; bi-dialectalism; bilingualism